Tranexamic acid in severe trauma patients managed in a mature trauma care system. Issue 6 (June 2018) - Boutonnet, Mathieu; Abback, Paer; Le Saché, Frédéric; Harrois, Anatole; Follin, Arnaud; Imbert, Nicolas; Cap, Andrew P.; Trichereau, Julie; Ausset, Sylvain
Abstract : BACKGROUND: Tranexamic acid (TXA) use in severe trauma remains controversial notably because of concerns of the applicability of the CRASH-2 study findings in mature trauma systems. The aim of our study was to evaluate the outcomes of TXA administration in severely injured trauma patients managed in a mature trauma care system. METHODS: We performed a retrospective study of data prospectively collected in the TraumaBase registry (a regional registry collecting the prehospital and hospital data of trauma patients admitted in six Level I trauma centers in Paris Area, France). In hospital mortality was compared between patients having received TXA or not in the early phase of resuscitation among those presenting an unstable hemodynamic state. Propensity score for TXA administration was calculated and results were adjusted for this score. Hemodynamic instability was defined by the need of packed red blood cells (pRBC) transfusion and/or vasopressor administration in the emergency room (ER). RESULTS: Among patients meeting inclusion criteria (n = 1, 476), the propensity score could be calculated in 797, and survival analysis could be achieved in 684 of 797. Four hundred seventy (59%) received TXA, and 327 (41%) did not. The overall hospital mortality rate was 25.7%. There was no effect of TXA use in the whole population but mortality was lowered by the use of TXA in patients requiring pRBC transfusion in the ER (hazard ratio, 0.3; 95% confidence interval, 0.3–0.6). CONCLUSION: The use of TXA in the management of severely injured trauma patients, in a mature trauma care system, was not associated with reduction in the hospital mortality. An independent association with a better survival was found in a selected population of patients requiring pRBC transfusion in the ER. LEVEL OF EVIDENCE: Therapeutic study, level III. Abstract : Supplemental digital content is available in the text.